Efektivitas Pembelajaran Al-Qur’an: Qira’at ‘Ashim Riwayat Hafsh Thariq Asy-Syathibiyyah Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Mahasiswa Universitas Ptiq Jakarta - Salim, Muhsin; Alwi, Wildan (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2024)
This study aims to determine the effectiveness of learning the Qur'an (tahsin tilawah) specifically in Qira'at 'Ashim Riwayat Hafsh Thariq Asy-Syathibiyyah to improve students' ability to read the Qur'an. This type of research is qualitative descriptive research. The subjects of this study were students of the Islamic Religious Education (PAI) study program, Faculty of Tarbiyah and Teacher Training, PTIQ University, Jakarta, class of 2019. Data collection techniques in this study were: interviews and documentation. The results of the study showed that learning the Qur'an: qira'at 'Ashim sejarah Hafsh thariq asy-Syathibiyyah to improve the ability to read the Qur'an of PTIQ University Jakarta students, especially students of the PAI study program, Faculty of Tarbiyah and Teacher Training, class of 2019, was classified as effective, reflected in the number of students who were able to complete their studies at the end of the semester, where the ability to read the Qur'an properly and correctly is one of the requirements for graduation at PTIQ University, Jakarta, in accordance with the Rector's Decree. This is tested with a tahsin exam in which the reading used is in accordance with the qira'at 'Ashim narrated by Hafsh Tariq asy-Syathibiyyah.